INFLUENCE OF COMPETENCY AND FACILITIES TOWARDS INPATIENT PATIENT SATISFACTION AT PUBLIC HEALTH CENTER IN INDRAGIRI HULU REGENCY - Aris Triyono; Suwaji Suwaji (JURNAL MANAJEMEN DAN BISNIS, 2020)
Research is conducted at the health center in Indragiri Hulu Regency Province of Riau. To test and analyze the influence of Competence and Support infrastructure on the satisfaction of patients hospitalized patients. To test and analyze the effect of compensation on the satisfaction of patients hospitalized patients. To test and analyze the influence of Means of infrastructure on patients' satisfaction at the Indragiri Hulu Regency health center. With a population of 3,618 patients hospitalized inpatient and sample 98. The data used are primary data and secondary, collecting the data with the deployment of questionnaires and engineering documentation. Analysis of the data used in the study is that the analysis of descriptive and analytical quantitative. The data analysis technique is the Instrument Test, Validity Test, Reliability Test. Classical Assumption Test; Normality Test; Linearity Test; Multicollinearity Test; Heteroscedasticity Test. And Analysis Regression Linear Regression with program SPSS 21. The study results showed that the competence and facilities infrastructures are simultaneously influenced significantly to the satisfaction of patients hospitalized inpatient. Competence is partially influenced significantly to the satisfaction of patients hospitalized inpatient. Facility Infrastructure is partially influenced significantly to patient satisfaction in health centers in the  Indragiri Hulu Regency. The coefficient of determination(R2) contribution of variable competence and facilities infrastructure is simultaneous to the variable satisfaction of patient care hospitalization by 23.3%, and the remaining 76.7% is influenced by variables other was not examined in the study of this.